Exploring the causal effect of cosmic filaments on dark matter haloes - Storck, Anatole; Cadiou, Corentin ; 0000-0003-2285-0332; Agertz, Oscar; Galárraga-Espinosa, Daniela (Monthly Notices of the Royal Astronomical Society, 2025)
The way in which the large-scale cosmic environment affects galactic properties is not yet understood. Dark matter haloes, which embed galaxies, initially evolve following linear theory. Their subsequent evolution is driven by non-linear structure formation in the halo region and in its outer environment. In this work, we present the first study where we explicitly control the linear part of the evolution of the halo, thus revealing the role of non-linear effects on halo formation. We focus specifically on the effect of proximity to a large cosmological filament. We employ the splicing method to keep fixed the initial density, velocity, and potential fields where a halo will form while changing its outer environment, from an isolated state to one where the halo is near a large filament. In the regime of Milky Way-mass haloes, we find that mass and virial radius of such haloes are not affected by even drastic changes of environment, whereas halo spin and shape orientation with respect to a massive filament is largely impacted, with fluctuations of up to 80 per cent around the mean value. Our results suggest that halo orientation and shape cannot be predicted accurately from a local analysis in the initial conditions alone. This has direct consequences on the modelling of intrinsic alignment for cosmic shear surveys, like Euclid. Our results highlight that non-linear couplings to the large-scale environment may have an amplitude comparable to linear effects, and should thus be treated explicitly in analytical models of dark matter halo formation.
Keywords: (cosmology:) dark matter; (cosmology:) large-scale structure of the Universe; galaxies: haloes